0420 Evaluating the Association Between Life Events, Perceived Stress, and Insomnia Status: Data from a National Cohort of Good Sleepers (The NITES Study). (27th April 2018) - Gencarelli, A M; Vargas, I; Khader, W; Muench, A; Boyle, J T; Morales, K; Grandner, M A; Ellis, J; Kloss, J D; Perlis, M L
Abstract: Introduction: Stressful life events are widely thought to trigger (precipitate) acute insomnia (AI). The role of chronic stress and/or perceived stress has not been extensively evaluated for their potential as perpetuating factors for insomnia. The current study investigated differences in life events and perceived stress in good sleepers [GS], subjects with AI that recovered [REC], persist poor sleepers [PPS], and subjects with chronic insomnia [CI]. Methods: A national cohort of 1, 069 subjects who were corroborated as good sleepers were tracked for a period of one year and assessed for changes in insomnia status. Sleep diaries were completed on a daily basis and Perceived Stress Scales (PSS) and Life Event Scales (LES) on a weekly basis. Using the diary data, groups were identified by "transition" (REC, PPS, or CI). Quartile means were obtained for each scale (PSS and LES) and a 4 [group] x 4 [time] mixed model analysis was performed. Results: While, there were no significant differences based on time, there was a significant main effect of group for both stress measures. For LES, the REC group reported a greater number of average life events ( p < .001), whereas, for PSS, the CI group reported higher levels of perceived stress ( p < .001) as compared to the other 3 groups. Conclusion: Despite reporting the least number of life events, the CI group rated their perceived stress as highest. These results suggest that the CI group may be less able to cope with life stressors. In contrast, the REC group may be better equipped to cope with life events and thus experience them as less stressful. Alternatively, because life events can be interpreted as either positive or negative, the REC group may be experiencing a greater number of positive events that are buffering their self-reported stress. Support (If Any): Perlis: NIH R01AG041783 & Ellis: Economic and Social Research Council (RES-061-25-0120-A).